The mechanism of mild traumatic brain injury based on diffusion tensor imaging - Fang-xu TAO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Objective To analyze the correlation between diffusion tensor imaging (DTI) and neuropsychological tests in patients with mild traumatic brain injury (mTBI), and to explore the damage mechanism of acute mTBI. Methods A total of 16 mTBI patients and 15 sex-, age- and education-matched healthy controls were scanned at 3.0T MRI, including T1WI, T2WI, T2-FLAIR and DTI. Voxel-based morphometry (VBM) was used to calculate fractional anisotropy (FA), mean diffusivity (MD) and apparent diffusion coefficient (ADC). Neuropsychological tests including Beck Depression Inventory (BDI), State Anxiety Inventory (SAI) and Trait Anxiety Inventory (TAI) were performed. Spearman rank correlation analysis explored the correlation between FA, MD, ADC values and neuropsychological tests. Results Compared with control group, FA value was decreased in supplementary motor area (SMA) of right frontal lobe, and increased in precentral gyrus and supramarginal gyrus of right frontal lobe and right parietal lobe; MD value was increased in bilateral frontal lobes, parietal lobes and right cingulate gyrus; ADC value was increased in bilateral frontal lobes, right parietal lobe and insular lobe in mTBI group. SAI score in mTBI group was significantly higher than that in control group [20.50 (13.25, 29.75) score vs. 11 (8, 12) score; Z = -3.493, P = 0.000), while BDI and TAI scores had no significant difference between 2 groups (P > 0.05, for all). Spearman rank correlation analysis showed there was no correlation between FA (rs = 0.369, P = 0.478), MD (rs = 0.295, P = 0.421) and ADC (rs = 0.401, P = 0.394) values of abnormal brain regions and SAI score. Conclusions DTI parameters and related neuropsychological changes of multiple brain regions exist in acute mTBI. This study suggest that DTI can serve as a potential biomarker of mTBI.